KINERJA GURU SEKOLAH LUAR BIASA DALAM PEMBELAJARAN DI KELAS DI YAYASAN TARBIYAT Ul MUTA’ALIMIN KABUPATEN SUBANG - Catur Herry Wibawa (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2012)
AbstractTeacher is a responsible person for disciplining children especially children with disability. He or she must have  a good performances so the children and people with disability behaviour level not deviate from the norms in society. Refer to that of  such big role, researcher is attracted to conduct a study to describe how the Special School Teacher’s performance in the classroom process in Tarbiyat Ul Muta’Alimin Institution Subang Regency. The scope of the study is about quality of work dimension with the following indicators: Provision of work, Ability to work level, Ability to analyze data, Ability to evaluate complaint, Consumers objection and work result. Especially, quantity work dimension with the following indicators: Working time, Work attendance, Pace of work and Level of Accuracy. The study design used quantitative and descriptive method. The target population in this study is a teacher who works as educator in Special School of Tarbiyat Ul Muta’Alimin Institution Subang Regency which numbered 20 people. In determining the sample, researcher uses census technique.All of the performance aspect, the result showed that the special school teacher performance in the classroom process in Tarbiyat Ul Muta’Alimin Institution Subang Regency are not optimal. This is because of lack of their understanding on the management and provision of special needs children education and lack of non formal education on special children needs. Teacher performance problems in the Tarbiyatul Muta’Alimin Subang Regency, classroom process is the less inability of teacher in handling of the learning problems to their students because they don’t understand special need children character.  Keywords : teacher  performance,  difabel,  special school,  classroom teaching AbstrakGuru sebagai penanggung jawab pendisiplinan anak khususnya penyandang cacat harus mempunyai kinerja yang baik agar tingkat laku anak/ penyandang cacat  tidak menyimpang dengan norma yang berlaku di masyarakat. Dengan  peran guru yang begitu besar tersebut, peneliti tertarik untuk mengadakan penelitian. Tujuan penelitian untuk menggambarkan kinerja  Guru Sekolah Luar Biasa (SLB) dalam pembelajaran di kelas di Yayasan Tarbiyat Ul Muta’Alimin Kabupaten Subang. Ruang lingkup penelitian tentang dimensi kualitas kerja, dengan indikator: ketepatan kerja, tingkat kemampuan  bekerja, kemampuan menganalisis data, kemampuan mengevaluasi keluhan, keberatan konsumen dan hasil kerja. Termasuk juga dimensi kuantitas kerja, dengan indikator: waktu kerja, absensi kerja, kecepatan kerja dan tingkat ketelitian.Desain penelitian yang digunakan dalam penelitian ini adalah kuantitatif dengan metode deskriptif, Populasi yang menjadi sasaran dalam penelitian ini adalah guru yang bekerja sebagai pendidik di SLB  Yayasan Tarbiyat Ul Muta’Alimin  Kabupaten Subang  yang berjumlah 20 orang. Dalam menentukan sampel peneliti menggunakan teknik sensus. Hasil penelitian semua aspek kinerja tesebut diatas  menyatakan bahwa kinerja guru SLB dalam pembelajaran di kelas di Yayasan Tarbiyat Ul Muta’Alimin Kabupaten Subang belum optimal,  dikarenakan masih kurang pahamnya guru terhadap penanganan dan pemberian pendidikan terhadap anak berkebutuhan khusus dan kurangya pendidikan non formal terhadap penanganan anak berkebutuhan khusus, serta tidak memahami karakter siswa berkebutuhan khusus.